As Mulheres em O Tempo e o Vento de Erico Verissimo - Portella, Lavinia Guimarães (2011)
This work intends to analyse the role of the time as one of the pillars elements in the book The time and the wind and, through the work, invites the reader to think about the history written by ourselves everyday. Considered an Erico Verissimo s masterpiece, the novel shows a circular structure, what suggests a non-linear connection with the time. So, this work, in the first moment, analyses the resources used by the author to create, characterize and intensify the cyclic shape of his work. As in the cycle, the novel produces a constant coming and going movement, that goes back from the present to the past and vice versa. Inside of the most important cycle, the work shows others circles as the cycle that goes from the history to the fiction, like a inseparable continuum and causes a dialogue between epic, an old style of writing, and the novel, created through the distance epic s dissolution. This connection provokes an analysis of the narrator and his role and a discussion about the literary work. The study of the time in this novel shows the trilogy s central feminine characters: Ana Terra, Bibiana and Maria Valéria. Guardians of the time, they represent it in the work because they experience a special connection with the past. The analysis of personality and feminine actions shows how the Terra women s job, sexuality, religion and the strenght have ancestral support in the time, a connection that can teach a lot of things to the readers in the 21st century, who live a cultural standardization process. In 2011, when it celebrates 50 years, it is possible to say that Erico Verissimo s masterpiece - The time and the wind stays extremely up-to-dated to make readers think about the world where they are living in.